THE IMPORTANCE OF KI67, GLIAL FIBRILLAR ACIDIC PROTEIN AND VITAMIN D RECEPTOR IN THE CENTRAL NERVOUS SYSTEM OF POSTMORTEM SUICIDE CASES - Cavlak, Nevin; Turkoglu, Abdurrahim; Bork, Turgay; Ozercan, Ibrahim Hanifi (Romanian Legal Med Soc, 2022)
Death by suicide is a tragic public health problem. Major depressive patients constitute some of these deaths. Although the etiology of major depression has not been clarified, there are studies suggesting that the hippocampus and caudate nucleus may be effective. In this study, it was aimed to compare vitamin D receptor (VDR), Ki67 and glial fibrial acidic protein (GFAP) antibodies in the brain tissues (hippocampus and caudate nucleus) of untreated major depression patients who died because of suicide with the control group. Left hippocampus and caudate nuclei of seven patients with untreated major depression who died of suicide in a one-year period and six psychiatrically normal patients were taken during autopsy. The hippocampus was stained with VDR, GFAP and Ki67 antibodies, and the caudate nucleus was stained with VDR and GFAP antibodies. There was no significant difference in the number of Ki67-positive cells in the anterior and posterior dentate gyrus between the major depression and control groups (P > 0.05). In the major depression group, a negative correlation was reported between the number of Ki67-positive cells in the anterior dentate gyrus and age (r: 0.867, P < 0.05). In the anterior dentate gyrus, posterior dentate gyrus and caudate nucleus, there was no significant difference between the suicide and control groups in the fraction of the immunoreactive area with GFAP antibodies (P > 0.05). While the percentage of immunoreactive granular cells for vitamin D receptor in the anterior dentate gyrus was significantly higher than the control group (P <0.05), no significant difference was reported in the posterior dentate gyrus. Vitamin D receptor immunoreactive neuron positivity in the caudate nucleus was not significantly different between the major depression and control groups (P > 0.05). In untreated major depression, additional immunohistochemical changes are observed in the anterior hippocampus, and the vitamin D receptor increases in the granular cells as a protective factor.
Keywords: Suicide; hippocampus; vitamin D receptor; caudate nucleus